Effect of Bowel Preparation to Colonoscopy Interval on Preparation Quality and Colonoscopy Outcomes: A Meta-Analysis - Gao, Ying; Lin, Xi-jie (Turkish Journal of Gastroenterology, 2022)
Background: This study evaluates the effect of bowel preparation to colonoscopy time interval on quality of bowel preparation and outcomes of colonoscopy. Methods: Studies were identified after a literature search in electronic databases and were selected for inclusion based on precise eligibility criteria. Meta-analyses of proportions were performed to achieve overall bowel preparation adequacy and adenoma/polyp detection rates. Odds ratios depicting associations between bowel preparation quality and bowel preparation to colonoscopy time were pooled to achieve an overall estimate. Results: Twenty studies (10 341 individuals subjected to colonoscopy) were included. Bowel preparation adequacy rate was higher with shorter (94% [95% CI: 91, 97]) than with longer (84% [95% CI: 79, 89]) interval between bowel preparation and colonoscopy. In a subgroup analysis, 20 hours intervals were associated with 94% [95% CI: 92, 97], 92% [95% CI: 86, 96], 85% [95% CI: 77, 91], and 85% [95% CI: 75, 92] adequacy rates, respectively. A pooled analysis of odds ratios also showed that bowel preparations adequacy was significantly better with shorter bowel preparation to colonoscopy time (odds ratio 1.69 [95% CI: 1.23, 2.15]). There was no significant difference in adenoma detection rate between shorter (18% [95% CI: 9, 29]) and longer (19% [95% CI: 15, 22]) bowel preparation to colonoscopy intervals. Polyp detection rate was higher with shorter (47% [95% CI: 27, 68]) than with longer (30% [95% CI: 24, 38]) bowel preparation to colonoscopy interval. Conclusion: A shorter interval between bowel preparation and colonoscopy led to a higher bowel preparation adequacy rate which was also associated with a higher polyp detection rate. Cite this article as: Gao Y, Lin XJ. Effect of bowel preparation to colonoscopy interval on preparation quality and colonoscopy outcomes: A meta-analysis. Turk J Gastroenterol. 2023; 34(1): 26-34.